2006
DOI: 10.1039/b513329g
|View full text |Cite
|
Sign up to set email alerts
|

Novel highly selective catalytic oxychlorination of phenols

Abstract: The highly selective oxychlorination of various phenols catalyzed by CuCl2 under mild conditions, in which chloride ions are used as chlorinating agents and dioxygen as a final oxidant, has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 10 publications
(7 reference statements)
1
40
0
1
Order By: Relevance
“…[27][28][29] However, we observed that non-phenolic compounds were not reactive in these reactions; moreover, phenols having electron-withdrawing substituents also did not react at all. A suggested explanation was a necessary formation of Cu(II) (phenolate) complexes as key intermediates, in which a rate-determining one-electron oxidation of phenolate by Cu(II) to the corresponding phenoxy radicals took place.…”
Section: Introductionmentioning
confidence: 67%
“…[27][28][29] However, we observed that non-phenolic compounds were not reactive in these reactions; moreover, phenols having electron-withdrawing substituents also did not react at all. A suggested explanation was a necessary formation of Cu(II) (phenolate) complexes as key intermediates, in which a rate-determining one-electron oxidation of phenolate by Cu(II) to the corresponding phenoxy radicals took place.…”
Section: Introductionmentioning
confidence: 67%
“…We have recently communicated a remarkable activity of CuCl 2 to catalyze under mild conditions oxychlorination of various phenols with dioxygen affording monochlorinated products [19]. In the present work we report the results of the systematic study of this novel highly chemo-and regioselective reaction.…”
Section: Introductionmentioning
confidence: 93%
“…The reaction of phenol (1 e) with 2 equivalents of LiCl in the presence of O 2 and 12 mol % CuCl 2 in acetic acid at 80 8C resulted in 93 % conversion and 90 % selectivity towards 4-chlorophenol (173 e; Scheme 61). [177] Analogously, the oxidative bromination of various phenols was performed with LiBr and a catalytic amount of Cu(OAc) 2 ; however, the para regioselectivity was generally lower for bromination than for chlorination. [178] The presence of a hydroxy group on the aromatic nucleus is essential for the reactivity of the aromatic substrate.…”
Section: Nitrogen Compounds As Catalysts For Aerobic Oxidative Halogementioning
confidence: 99%